Securing and Managing the Data with efficient Architecture in Cloud Computing Environment - log, kartheesan; Srivatsa, S. K. (Journal of Advanced Computer Science & Technology, 2013)
Cloud computing technology and services has become an important issue in the recent years. Cloud Computing needs lot of attention, time and innovative concepts for the technology to mature over a period of time. Many organizations show interest in adopting cloud computing technology and services because of its socio economic and time factor. Cloud computing is nothing but virtual centralization of different computers where the software and memory space is provided by the vendor and the data is managed by them. This leaves the client/customer unaware of where the process is running or where the data is stored. Security of the data is highly dependent on the vendor who has to provide an assurance to the customer on security issues by making service level agreements. This paper focus on security issues, requirements for providing a secured data in cloud computing environment by giving a standard service oriented cloud computing Architecture and management tools that can be used by the organizations for authentication, confidentiality and integrity. Thus providing secured data access and transfer.